2019
DOI: 10.1021/acs.jmedchem.9b00875
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism by Aldehyde Oxidase: Drug Design and Complementary Approaches to Challenges in Drug Discovery

Abstract: Aldehyde oxidase (AO) catalyzes oxidations of azaheterocycles and aldehydes, amide hydrolysis, and diverse reductions. AO substrates are rare among marketed drugs, and many candidates failed due to poor pharmacokinetics, interspecies differences, and adverse effects. As most issues arise from complex and poorly understood AO biology, an effective solution is to stop or decrease AO metabolism. This perspective focuses on rational drug design approaches to modulate AO‑mediated metabolism in drug discovery. AO bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 236 publications
1
70
0
Order By: Relevance
“…25 Potential DDIs between these drugs and favipiravir should be carefully monitored. Several drugs, such as citalopram, 26 zaleplon, 27 famciclovir, 28 and sulindac, 29 are also metabolized by AO. In vitro study shows that favipiravir is a mechanism based inhibitor of AO in a concentration-dependent manner between 3.14 and 942 µg/mL 15 and the previous clinical study showed a mean steady-state trough concentration of 46.1 µg/ mL in the treatment of EVD.…”
Section: Regarding Potential Drug-drug Interaction In Pharmacokineticsmentioning
confidence: 99%
“…25 Potential DDIs between these drugs and favipiravir should be carefully monitored. Several drugs, such as citalopram, 26 zaleplon, 27 famciclovir, 28 and sulindac, 29 are also metabolized by AO. In vitro study shows that favipiravir is a mechanism based inhibitor of AO in a concentration-dependent manner between 3.14 and 942 µg/mL 15 and the previous clinical study showed a mean steady-state trough concentration of 46.1 µg/ mL in the treatment of EVD.…”
Section: Regarding Potential Drug-drug Interaction In Pharmacokineticsmentioning
confidence: 99%
“…9,22 Many AO substrates report poor PKs with rapid metabolism and failed drug development. [23][24][25] Therefore, the auto-inhibition of AO is speculated to be necessary to maintain significant FPV concentration.…”
Section: Pharmacokinetics Of Fpv In Severe Covid-19mentioning
confidence: 99%
“…Some compounds generate genotoxicity without metabolic activation, whereas other compounds need metabolic activation to produce their genotoxic effect, such as N-nitrosodimethylamine [92]. When a compound undergoes metabolic activation, it changes the structure or electric charge of the original chemical [93,94]; given this fact, metabolites are usually more hydrophilic than the parental compounds. These metabolites are more likely to bind to DNA, leading to corrupt replication.…”
Section: Genotoxicitymentioning
confidence: 99%